2023
DOI: 10.1289/ehp11721
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lifetime Exposure to Glyphosate and Aminomethylphosphonic Acid (AMPA) with Liver Inflammation and Metabolic Syndrome at Young Adulthood: Findings from the CHAMACOS Study

Abstract: Background: The prevalence of liver disorders and metabolic syndrome has increased among youth. Glyphosate, the most widely used herbicide worldwide, could contribute to the development of these conditions. Objective: We aimed to assess whether lifetime exposure to glyphosate and its degradation product, aminomethylphosphonic acid (AMPA), is associated with elevated liver transaminases and metabolic syndrome among young adults. Methods: We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 80 publications
(101 reference statements)
0
4
0
Order By: Relevance
“… 9 “Chronic inflammation … can interfere with neuronal and glial well-being, leading to dysregulation of brain homeostasis and compromising cognition,” he says. More work is needed to understand the long-term consequences of glyphosate exposure, and this current work joins another recent study 4 showing that exposures early in life happen, and they are associated with harmful health outcomes.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“… 9 “Chronic inflammation … can interfere with neuronal and glial well-being, leading to dysregulation of brain homeostasis and compromising cognition,” he says. More work is needed to understand the long-term consequences of glyphosate exposure, and this current work joins another recent study 4 showing that exposures early in life happen, and they are associated with harmful health outcomes.…”
mentioning
confidence: 61%
“… The flower-growing industry employs about one-fifth of all adults left, in Pedro Moncayo County, right, and sprays more than 70 fungicides and pesticides according to the authors. The ESPINA study 4 is investigating secondary exposures of the county’s children and adolescents. Images: © GDA/AP Images, left, and Courtesy of Natura Films (Quito, Ecuador), right.…”
mentioning
confidence: 99%
“…Interestingly, when deposited in soil, glyphosate can be degraded mainly into aminomethylphosphonic acid (AMPA), mostly by microbial action, increasing its half-life up to 958 days, while that of glyphosate is only up to 280 days [ 11 ]. Moreover, AMPA has been detected in (i) the blood of patients after accidental ingestion of GBHs [ 12 ]; (ii) urine samples from Mexican farm workers [ 13 ] and Californian residents living near glyphosate-application zones, with the latter associated with liver and cardiometabolic disorders in childhood [ 14 ]; and (iii) brains of mice receiving pure glyphosate by the oral route [ 15 ]. With these lines of evidence and the idea that AMPA can be produced by humans or rodents via intestinal microbiomes [ 16 ], it is striking to note that most of the biological effects of AMPA remain essentially unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Initially considered harmless to humans, recent studies have revealed that glyphosate exposure is associated with a broad spectrum of health-related outcomes in both non-occupationally (Geier and Geier, 2023;Eskenazi et al, 2023;Hsiao et al, 2023;Qi et al, 2023a;Yang et al, 2023) and occupationally (Zhang et al, 2023;Chang et al, 2023) exposed populations. Given that some of these outcomes [i.e., endocrine-disruption (Lesseur et al, 2021;Geier and Geier, 2023), insulin-resistance (Eskenazi et al, 2023;Qi et al, 2023b), bone mineral health (Wang et al, 2023), or neuroaxonal damage (Yang et al, 2023)] are intimately related to biological systems that influence muscle health, we hypothesized that glyphosate exposure could be a risk factor for impaired muscle strength and physical function limitations in the general population. Our hypothesis is supported by experimental evidence indicating that glyphosate-based herbicide (GBH) exposure during development causes muscle fibrosis and decreases levels of neuromuscular junctions in the soleus muscle of mouse pups (Barbosa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%